Haemodynamic consequences of Spinal Anaesthesia for non-emergency Caesarean section - Dyer, Robert A (Department of Anaesthesia, 2014)
Single shot spinal anaesthesia for caesarean section is currently accepted as the favoured method in the absence of contraindications, for reasons of safety and comfort. Firstly, there is an increased risk of failed intubation associated with general anaesthesia. Secondly, spinal anaesthesia, if practiced correctly, allows for a superior experience of the delivery and improved bonding with the infant. Maternal haemodynamic stability is desirable both for maternal and neonatal safety, and to diminish maternal side-effects such as nausea and vomiting. Therefore, after an extensive literature review, clinically relevant aspects of spinal anaesthesia were studied, with a view to contributing to knowledge which could improve safety and outcome. The central themes explored in this thesis were fluid management during spinal anaesthesia for caesarean section in healthy parturients, the haemodynamic effects of the vasoactive agents ephedrine, phenylephrine and oxytocin during spinal anaesthesia for caesarean section in healthy patients and in patients with preeclampsia, and short term neonatal outcome after spinal anaesthesia in patients with severe preeclampsia. Research methodology included non-invasive measures as well as the use of a pulse wave form analysis monitor to measure maternal cardiac output. A validation study was performed comparing this method with thermodilution in patients with postpartum complications of preeclampsia. Abstract viii The results of these studies showed that: The pulse wave form monitor employed showed acceptable limits of agreement with the thermodilution method. Crystalloid coload was associated with lower vasopressor requirements than conventional preload. Spinal anaesthesia was associated with afterload reduction, which was more pronounced in healthy patients than in preeclamptics. Ephedrine maintained or increased, and phenylephrine reduced maternal cardiac output in healthy patients. Oxytocin was associated with transient haemodynamic instability in healthy and preeclamptic patients, which was obtunded by phenylephrine in the healthy population. Spinal anaesthesia for caesarean section was associated with a greater umbilical arterial base deficit than general anaesthesia in patients with preeclampsia. Overall, these studies should contribute to improved knowledge of haemodynamic responses during spinal anaesthesia for caesarean section, and ultimately to improved maternal morbidity and mortality.